2021
DOI: 10.1021/acs.jpcc.1c04596
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Signature of Metallophilic Interactions in [Pt(terpy)Cl][Au(CN)2]

Abstract: Metallophilic interactions, weak interactions between closed-shell metal atoms, have been recently utilized to create unique nanostructures with anisotropy of electronic properties along the direction of the interaction. The strength of the metallophilic interaction is an important factor for the design of these nanostructures. Recently, Doerrer and co-workers presented a general metathesis route to create extended chains of metallophilic double salts with two modular opposite-charge ions with Au­(I) and Pt­(I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Raman measurements in the 4 000–100 cm −1 range contain several peaks that originate from the organic ligand and cyanide stretching frequency, similar to those in the IR spectrum. However, several other reports have shown that two gold atoms are in close proximity and show the so‐called Au⋅⋅⋅Au stretching frequency located below 200 cm −1 [7b, 14] …”
Section: Resultsmentioning
confidence: 99%
“…Raman measurements in the 4 000–100 cm −1 range contain several peaks that originate from the organic ligand and cyanide stretching frequency, similar to those in the IR spectrum. However, several other reports have shown that two gold atoms are in close proximity and show the so‐called Au⋅⋅⋅Au stretching frequency located below 200 cm −1 [7b, 14] …”
Section: Resultsmentioning
confidence: 99%
“…Previously, we discovered that the photon density of the triplet emission decreases upon cooling and it is closely related to the Au⋯Au vibrations (110 cm −1 ). 55,68…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we discovered that the photon density of the triplet emission decreases upon cooling and it is closely related to the AuÁ Á ÁAu vibrations (110 cm À1 ). 55,68 To ascertain the thermosensitivity and usability of the thermal sensor, we evaluated the relative thermal sensitivity (S r ) by taking the first derivative of the fitted thermometric parameter D(T) calibration curve as a function of temperature: S r = (qD/qT)/D (Table S23, ESI †). S r was calculated for both thermometric parameters and two excitation energies concerning the temperature given in Fig.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…The computed potential energy surfaces demonstrating reasonable stabilization and concomitant curvature around the minima raises the question of whether the M′⋯M′ stretching may actually be experimentally observable. Very recently 43 the vibrational signature of the Au–Pt metallophilic interaction in [Pt(terpy)Cl][Au(CN) 2 ] was observed experimentally at 57 cm −1 . This system is well selected for this specific purpose due to the rigidity and the scarcity of obvious low-energy modes.…”
Section: Resultsmentioning
confidence: 99%